Solution conformation and flexibility of capsular polysaccharides from Neisseria meningitidis and glycoconjugates with the tetanus toxoid protein - Abdelhameed, Ali Saber; Morris, Gordon A.; Almutairi, Fahad; Adams, Gary G.; Duvivier, Pierre; Conrath, Karel; Harding, Stephen E. (Nature Publishing Group, 2016)
The structural integrity of meningococcal native, micro-fluidized and activated capsular polysaccharides and their glycoconjugates – in the form most relevant to their potential use as vaccines (dilute solution) - have been investigated with respect to their homogeneity, conformation and flexibility. Sedimentation velocity analysis showed that the polysaccharide size distributions were generally bimodal with some evidence for higher molar mass forms at higher concentration. Weight average molar masses Mw where lower for activated polysaccharides. Conjugation with tetanus toxoid protein however greatly increased the molar mass and polydispersity of the final conjugates. Glycoconjugates had an approximately unimodal log-normal but broad and large molar mass profiles, confirmed by sedimentation equilibrium “SEDFIT MSTAR” analysis. Conformation analysis using HYDFIT (which globally combines sedimentation and viscosity data), “Conformation Zoning” and Wales-van Holde approaches showed a high degree of flexibility – at least as great as the unconjugated polysaccharides, and very different from the tetanus toxoid (TT) protein used for the conjugation. As with the recently published finding for Hib-TT complexes, it is the carbohydrate component that dictates the solution behaviour of these glycoconjugates, although the lower intrinsic viscosities suggest some degree of compaction of the carbohydrate chains around the protein.